АКТИВНЫЕ РАЗЛОМЫ И ИНТЕНСИВНОСТЬ ЭКЗОГЕННЫХ ПРОЦЕССОВ НА РУССКОЙ РАВНИНЕ - Бронгулеев В.В. (My University, 1998)
Correlations between active faults and exogeodynamic processes on the East-European Plain were analyzed. The intensity of karst, landslides and erosion dissection appear to be almost independent of fault density – the impact of the active faults on the variations of the processes doesn't exceed several percents. More distinct correspondence may be seen when analyzing the strikes of the faults and configuration of the regions with different intensity of the processes. Their boundaries are to some extent controlled by active faults.

The influence of active faults' density on the exogeodynamics, though valuable in several local regions of the Plain, is small in comparison with the other tectonic and climatic factors.
Keywords: ПЛАТФОРМЕННАЯ РАВНИНА; АКТИВНЫЕ РАЗЛОМЫ; ЭРОЗИОННОЕ РАСЧЛЕНЕНИЕ; КАРСТ; ОПОЛЗНИ; КОРРЕЛЯЦИЯ; 551.4.044:551.4.042(47–924.8)